Terminology training at translation and interpreting departments in Turkey and beyond - (:unkn) unknown (My University, 2020)
The lack of curriculum oriented courses in Translation and Interpreting Departments required steps to be taken in the academic field. The views of the lecturer, the students’ views, and the curriculum analysis constitute the three pillars of the research. The study has been conducted among the lecturers (N=33) of the department of Translation Studies and Translation & Interpreting in Turkey as well as the junior and senior students (N=131) of theses departments. Two questionnaires were prepared for academic staff and students as a data collection tool. Their responses were analyzed through SPSS 26 program. In the qualitative phase, six instructors and six students in the study group voluntarily answered the structured interview questions. The responses obtained from these interviews were transferred to NVivo 11 program. In addition, secondary data on curriculum oriented courses were obtained and the inventory collection concerning courses given by the departments of Translation Studies, and Translation & Interpreting was gathered. The contents of the courses in the curriculums of these departments based in our country and in other countries were examined. Terminology courses were classified accordingly. In order to show the importance and the place of the terminology in the field of translation, this research is expected to be a guide to the need for a special place in terminology in translation training.
Türkiye’de ve diğer ülkelerde bulunan mütercim tercümanlık bölümlerinde terimbilim eğitimi
Keywords: Terminology; translation studies; translation and interpreting; translation technologies; term management tools; translation training; terminology training